INVESTMENTS IN HUMAN CAPITAL DEVELOPMENT AND THEIR IMPACT ON BUSINESS RESILIENCE DURING ECONOMIC SHOCKS (Development Service Industry Management, 2025)
The article examines the impact of investments in human capital development on enterprise resilience under economic and security shocks, particularly within the context of the war in Ukraine and the transformation of the global economic environment. It substantiates the thesis that employee development is a key factor in ensuring competitiveness and organisational adaptability, enabling firms to operate under uncertainty, maintain business continuity, and recover quickly after crises. The study highlights that traditional personnel management approaches are being replaced by strategic investment in employee competencies, fostering a culture of continuous learning, digital literacy, psychological resilience, and leadership capabilities.The paper synthesises findings from contemporary international and Ukrainian research on the relationship between human capital development and organisational resilience. It reviews practices of Ukrainian and global companies, demonstrating that systematic and large-scale programmes for professional training, retraining, and employee support correlate with operational stability, retention of key specialists, and the ability to implement innovative solutions. The authors propose a human-capital-based resilience assessment matrix that enables measuring the impact of staff development investments on organisational adaptability. An empirical analysis of open data from nine leading Ukrainian companies across different sectors confirms the positive effect of human capital investment on firms’ ability to operate under uncertainty and restore performance in the post-crisis period.The results emphasise the need to establish a comprehensive human capital development policy at both enterprise and national levels, alongside creating institutional conditions that support continuous learning, digital transformation, and employee psychological wellbeing. The study outlines future research directions, including developing standardised resilience assessment indicators, expanding the empirical evidence base, and deepening the analysis of causal links between human capital investments and enterprise performance.
Keywords: human capital; employee development; business resilience; economic shocks; organisational adaptability